The Rock Physics Handbook Tools for Seismic Analysis of Porous Media. - Mavko, Gary; Mukerji, Tapan; Dvorkin, Jack (Cambridge University Press, 2003)
Annotation The Rock Physics Handbook conveniently brings together the theoretical and empirical relations that form the foundations of rock physics, with particular emphasis on seismic properties. It also includes commonly used models and relations for electrical and dielectric rock properties. Seventy-six articles concisely summarize a wide range of topics, including wave propagation, AVO-AVOZ, effective media, poroelasticity, pore fluid flow and diffusion. The book contains overviews of dispersion mechanisms, fluid substitution, and Vp-Vs relations. Useful empirical results on reservoir rocks and sediments, granular media, tables of mineral data, and an atlas of reservoir rock properties complete the text. This distillation of an otherwise scattered and eclectic mass of knowledge is presented in a form that can be immediately applied to solve real problems. Geophysics professionals, researchers and students as well as petroleum engineers, well log analysts, and environmental geoscientists will value The Rock Physics Handbook as a unique resource.
Keywords: elektronické knihy; electronic books